2006
DOI: 10.1177/0018726706072866
|View full text |Cite
|
Sign up to set email alerts
|

The contested space of multinationals: Varieties of institutionalism, varieties of capitalism

Abstract: The article argues that institutionalist theory applied to multinationals focuses on the issue of ‘institutional duality’, that is, that within multinationals, actors are pressured to conform to the expectations of their home context whilst also being subjected to the transfer of practices from the home context of the MNC itself. This institutional duality leads to conflicts that can be labelled as forms of ‘micro-politics’. The head office managers transfer practices, people and resources to subsidiaries in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
245
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(263 citation statements)
references
References 46 publications
4
245
0
14
Order By: Relevance
“…However, Brewster, Wood and Brookes (2016) found that MNCs tended, in general, to be more cautious in departing from national norms than their local counterparts, and tended to be followers rather than leaders in terms of innovating new HRM practices. This would reflect the fact that MNCs enter particular markets because of the advantages they confer (Morgan and Kristensen 2006); hence, they would be less interested in challenging the status quo. Interestingly, those firms most aggressively driving change were those industries facing crises of competitiveness ; this would suggest that innovating in HRM might often represent a response to crisis rather than positive strategic choices to make successful firms even more so.…”
Section: The Development Of Comparative Hrmmentioning
confidence: 99%
“…However, Brewster, Wood and Brookes (2016) found that MNCs tended, in general, to be more cautious in departing from national norms than their local counterparts, and tended to be followers rather than leaders in terms of innovating new HRM practices. This would reflect the fact that MNCs enter particular markets because of the advantages they confer (Morgan and Kristensen 2006); hence, they would be less interested in challenging the status quo. Interestingly, those firms most aggressively driving change were those industries facing crises of competitiveness ; this would suggest that innovating in HRM might often represent a response to crisis rather than positive strategic choices to make successful firms even more so.…”
Section: The Development Of Comparative Hrmmentioning
confidence: 99%
“…ex., Bélanger et Edwards, 2006;Ferner et Tempel, 2006;Edwards, Colling et Ferner, 2007;Edwards et Bélanger, 2009) notamment dans les filiales (Bélanger et coll., 1999;Kristensen et Zeitlin, 2005;Bouquet et Birkinshaw, 2008a;Dorrenbacher et Geppert, 2009;Dorrenbacher et Gammelgaard, 2011). Dans ce contexte micropolitique où la MNC est vue comme un espace social transnational (Morgan, 2001), le processus de transfert apparaît comme une négociation sociale (Morgan et Kristensen, 2006) qui n'est pas uniquement fonction de finalités économiques mais aussi de ressources de pouvoir des acteurs et de leurs intérêts (Edwards et coll., 2007;Ferner et coll., 2012). Yahiaoui (dans Cazal et coll., 2010) explique, par exemple, le processus d'hybridation des pratiques RH transférées de la maison-mère vers les filiales tunisiennes par les différences institutionnelles et l'histoire entre les deux pays, mais aussi par la stratégie des acteurs locaux.…”
Section: Recension Des éCrits Et Perspectives Théoriquesunclassified
“…Learning between partners from different national contexts is inhibited by different ways of social interaction and different understandings (Morgan & Kristensen, 2006;Pak et al, 2009). If the partners have different organizational cultures, developing absorptive capacity is especially complex (Daghfous, 2004;Nti & Kumar, 2000;Tsai, 2001).…”
Section: Learning In Ijvsmentioning
confidence: 99%